2019
DOI: 10.1186/s12864-019-5617-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and abiotic stress-responsive pattern of heat shock transcription factor family in Triticum aestivum L.

Abstract: Background Enhancement of crop productivity under various abiotic stresses is a major objective of agronomic research. Wheat ( Triticum aestivum L.) as one of the world’s staple crops is highly sensitive to heat stress, which can adversely affect both yield and quality. Plant heat shock factors (Hsfs) play a crucial role in abiotic and biotic stress response and conferring stress tolerance. Thus, multifunctional Hsfs may be potentially targets in generating novel strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
90
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 77 publications
7
90
0
Order By: Relevance
“…The number of HSF family members appears to be unrelated to the genome size, e.g., 35 Hsfs were found in Chinese cabbage (485 Mb) and 137 Hsfs in pear (527 Mb) [21,52]. Previous studies identified 56 and 82 members of the wheat HSF family [32,53], but we identified 61 TaHsfs in this study. To understand these differences in the numbers of wheat HSF members identified, we blasted the protein sequences identified by Xue et al [32] and Duan et al [53] against the latest wheat reference genome (IWGSC V1.1) [43].…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…The number of HSF family members appears to be unrelated to the genome size, e.g., 35 Hsfs were found in Chinese cabbage (485 Mb) and 137 Hsfs in pear (527 Mb) [21,52]. Previous studies identified 56 and 82 members of the wheat HSF family [32,53], but we identified 61 TaHsfs in this study. To understand these differences in the numbers of wheat HSF members identified, we blasted the protein sequences identified by Xue et al [32] and Duan et al [53] against the latest wheat reference genome (IWGSC V1.1) [43].…”
Section: Discussionmentioning
confidence: 56%
“…These findings matched with the identification criteria employed in the present study, so they were excluded. In total, 41 common HSFs were identified in all three studies, but the classifications and names of some of these proteins differed in the studies by Xue et al [32] and Duan et al [53]. For example, TraesCS1A02G375600, TraesCS1D02G382900, and TraesCS1B02G396000 were renamed as TaHsfA6a-1, TaHsfA6a-2, and TaHsfA6a-3 in the present study because they belong to a homeologous group and are orthologous to rice Os10g28340 (A6a).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…At least 25 Hsfs were identified in maize in 2011 and the number of ZmHsfs reached 30 in 2016 (Lin et al, 2011;Guo et al, 2016). Xue et al reported that at least 56 Hsfs exist in wheat (Xue et al, 2014), but our recent analysis results suggested a larger amount (Duan et al, 2019). The large number of Hsfs family members in plant mean the complexity and diversity of Hsfs family.…”
Section: Discussionmentioning
confidence: 72%